Elementos químicos y su relación con los errores refractivos en los trabajadores de lubricadoras en la ciudad de Babahoyo, junio -octubre 2023 - Ciza Haro, Gissela Maribel (2023)
In this paper we will address the relationship between exposure to chemical elements and refractive errors in workers of lubrication plants located in the city of Babahoyo. The main objective is: To analyse the relationship between exposure to chemical elements and refractive errors among workers in lubrication plants in the city of Babahoyo. The research carried out in this project is descriptive and exploratory in nature. A combination of bibliographic and field methods was used. The present study was carried out with 24 lubricator workers who met our inclusion and exclusion criteria. Data collection techniques include observation sheets, visual acuity tests, and questionnaire surveys. Data collected are tabulated using IBM SPSS version 25 statistical software. It is found that only men work in lubrication plants, 58% are under 30 years old, they are exposed to chemicals for 4-6 hours (25%), most of them for more than 6 hours. 100% of the respondents had symptoms and signs such as irritation and tearing. Eye irritation is the most prevalent symptom among workers exposed to chemicals. Exposure to chemical products is prolonged and has a direct impact on the appearance of discomfort among workers, it is recommended to implement policies focused on promoting the care and protection of the eyes.